Associations of serum sodium, potassium and chloride levels with the all-cause and cardiovascular diseases mortality among patients with depression - Qingping Zeng; Siqi Jia; Yu Li; Fei She; Ping Zhang (PLoS ONE, 2025)
Background Electrolyte disturbances are relatively common in patients with depression, but they are often overlooked, and the relationship between electrolyte changes and adverse outcomes in depression is not yet clear. This study aims to explore the impact of serum electrolyte levels on the all-cause and cardiovascular disease (CVD) mortality rates in patients with depression. Methods This prospective cohort study included 3127 patients with depression who participated in the National Health and Nutrition Examination Survey (NHANES) from 2005 through 2018. Depression was assessed using the Patient Health Questionnaire (PHQ-9), with a PHQ-9 score ≥10 defined as depression. The data were analyzed from April 1 to July 30, 2024. Multivariable Cox proportional hazards regression model was used to calculate the hazard ratios (HRs) and 95% confidence intervals (CIs) between serum sodium, potassium, and chloride levels and the CVD risk and all-cause mortality in patients with depression. Three multivariable models were constructed. We further stratified the analysis by age, gender, hypertension, smoking, alcohol consumption, diabetes, and drinking status. Interaction significance was estimated using P-values for the product terms between serum sodium, potassium, chloride, and stratification factors. Results This cohort study included data from 2946 participants in the analysis (mean [SD] age, 50.13 [16.48] years; 1116 men [37.88]); During a median (IQR) follow-up of 7.2 (3.6–10.5) years, 398 deaths were recorded, of which 117 were attributed to CVD.After multivariable adjustment, compared with participants in the first quartile of serum sodium levels, the HRs of CVD mortality were 0.90(95% CI, 0.53–1.53) in the fourth quartile (p for trend = 0.484). The HRs of all-cause mortality were 0.73(95% CI, 0.55–0.99) for the fourth quartile (p for trend = 0.003). A nonlinear association was observed between serum sodium levels and all-cause mortality in patients with depression (p for overall = 0.003, p for nonlinear = 0.047). Compared with participants in the first quartile of serum potassium levels, the HRs of CVD mortality were and 1.58(95% CI, 0.98–2.54) in the fourth quartile (p for trend = 0.050), the HRs of all-cause mortality were 1.52(95% CI, 1.16–1.99) for the fourth quartile (p for trend <0.001). A nonlinear association was observed between serum potassium levels and all-cause (p for overall<0.001, p for nonlinear = 0.005) and CVD (p for nonlinear = 0.003) mortality in patients with depression. Compared with participants in the first quartile of serum chlorine levels, the HRs of CVD mortality were 0.84(95% CI, 0.49–1.46) in the fourth quartile(p for trend = 0.284). The HRs of all-cause mortality were 0.70(95% CI, 0.51–0.95) for the fourth quartile(p for trend <0.001). A nonlinear association was observed between serum chlorine levels and all-cause (p for nonlinear<0.001) and CVD (p for nonlinear<0.001) mortality in patients with depression. Conclusion and correlations This cohort study found that in patients with depression, higher sodium is significantly correlated with lower all-cause mortality, higher potassium is significantly correlated with higher all-cause and CVD mortality, and higher chloride is significantly correlated with lower all-cause and CVD mortality.